Hak Dan Kewajiban Orang Tua Dalam Fikih Hadlonah Perspektif Pendidikan Islam - Muhtarom; Rasti Amelia; Cindi Eka Marsinia; Fani Afrianti; Ayu Sulastri; Siti Haura Najwa (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The concept of hadlonah in Islamic family law is often limited to formal-legal disputes over child custody following a divorce, creating a research gap regarding its integration into the family educational framework. This study aims to analyze the concept of hadlonah in Islamic jurisprudence, examine the rights of children and the obligations of parents, and explain its relevance to the implementation of Islamic education within the family. This study employs a qualitative approach with a library research design. Data collection was conducted through documentation studies of Quranic verses and relevant scientific journals. The collected data were then analyzed using thematic analysis with a descriptive-analytic presentation. The findings reveal that hadlonah is not merely a biological or technical custody right, but a holistic educational responsibility encompassing physical, psychological, moral, and spiritual dimensions. The study shows that the successful implementation of hadlonah requires active collaboration between both parents, which remains fully obligatory even in post-divorce conditions. In the context of Islamic education, hadlonah serves as the primary medium for character building and faith cultivation through daily habits and parental role-modeling, adapted to the child's developmental stages. This study implies that parents must view hadlonah as an integrated educational mandate to protect children from contemporary digital and social challenges.